A desk spectrofluoremeter for in-vivo and in-situ biological measurements - Moreno García., E.; de la Rosa Vázquez, J. M.; Fabíla Bustos., D. A.; Pérez Gutiérrez., N.; Mujica Asencio., C.; Domínguez-Cherit., J. (Revista Mexicana de Ingenieria Biomedica, 2009)
Fluorescence methods are being widely used in the lab for the measurement of species concentrations. Such measurements are normally expensive and time consuming because of preparative procedures and they are not done under in vivo and in situ conditions. Here we present a portable fluorescence system based in a mini-spectrometer, led’s as light sources, a bifurcated fiber optic and a laptop. The spectrofluorimeter is useful to measure the substances fluorescence in-vivo and in-situ, such as human tissue and any other organic and non-organic material. The system is controlled by the laptop from a program written in the graphical language G of the LabVIEW 7.1, which measures and process the spectra in real time. We show measurements with a 200 mW UV led (365 nm).